ASUPAN PURIN DAN TINGKAT PENGETAHUAN DENGAN KADAR ASAM URAT DI PUSKESMAS RURUKAN KOTA TOMOHON - Yuli Runtuwene; Rudolf B. Purba; Phembriah S. Kereh (POLTEKKES KEMENKES MANADO, 2016)
Uric acid is the end result of purine metabolism is one of the components of nucleic acidscontained in the nucleus of cells. needs purines recommended that 50 g / day - 100 g /day. It said purine intake over consumption of food sources of purines more than 100 g /day. Knowledge plays an important role in a person's behavior towards the disease. Thepurpose of this study is to determine the relationship of purine intake and level ofknowledge with uric acid levels in Puskesmas Rurukan Tomohon.This type of research is descriptive analytic research with this type of cross sectionalstudy in Puskesmas Rurukan Tomohon in February 2016. The sampling method ispurposive sampling which amounted to 37 samples and analysis using chi square test.According to the research community purine intake by Rurukan Tomohon were 19 people(51.4%) consume food sources of purines over 100 grams / day, 11 people (29.7%)consume enough food sources of purines that is 50-100 grams / day and 7 (18.9%)consume food sources of purines less than 50 grams / day. Based on the level ofknowledge that 9 (24.4%) of respondents had good knowledge, 14 people (37.8%) ofrespondents have sufficient knowledge and 14 people (37.8%) of respondents have lessknowledge.In conclusion there is a relationship between the intake of purine to uric acid kada andthere is a correlation between the level of knowledge with uric acid levels.